Scanning Electron Microscopy Investigation for Monitoring the Emulsion Deteriorative Process and Its Applications in Site-Directed Reaction with Paper Fabric - Liewei Qiu (MDPI AG, 2021)
The O/W isocyanate emulsion can be used as a sizing agent to improve the waterproof performance of paper. However, the -NCO content in the emulsion diminishes with the prolongation of standing time. What is happening to this seemingly stable emulsion, especially concerning its microstructure evolution? We propose to monitor the emulsions deteriorative process by combining freeze-drying technique and SEM. Thus, the emulsion containing -NCO active group was obtained by the synthetic polymer emulsification of HDI trimers. The results of SEM demonstrate that the emulsion deteriorative process actually represents the collapsing and fusion of stable honeycomb structure with the prolongation of standing time and increasing temperature. This is possibly due to the fact that the inner aggregative HDI trimers are reacting with outside water to form urethane macromolecules, and this results in the collapsing and fusion of the honeycomb structure, as observed in SEM images. Moreover, the measurement results of -NCO content and FT-IR spectroscopy present the -NCO content as reducing with increasing standing time and temperature. This conclusion further proves our hypotheses. Additionally, the emulsions are used to treat the paper by site-directed reaction. The results show that the with the increase of the standing time and temperature, the contact angles and surface free energy show a decrease and an increase, respectively, whereas surface free energy appeared at a minimum of 29.19 mJ·m−2 when the standing time and temperature was 1 h and 25 °C.